2011
DOI: 10.5510/ogp20110100059
|View full text |Cite
|
Sign up to set email alerts
|

Superstability of surface nanobubbles

Abstract: В последние годы, многочисленные эксперимен-ты показали существование наноскопических мягких доменов на поверхности раздела жидкость -твердое тело, смотрите работы [1 -10] и ссылки к ним. В большинстве экспериментов используют атомную силовую микроскопию (АСМ) [1 -8], но и другие методы [9, 10] также использовались. Самое после-довательное толкование этих экспериментов то, что мягкими доменами, которые походят на сегмент сферы с высотой порядка 10 нм и диаметром порядка 100 нм, являются так называемые поверхн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 19 publications
(42 reference statements)
1
52
0
Order By: Relevance
“…If this scenario is true, prediction of the actual population of cavitation bubbles in practical situations will require that, among other things, one know not only the initial distribution of cavitation nuclei but also their dynamic behavior in which bubble-bubble interaction plays a significant role. Also, the present findings may be relevant to the study of the superstability of nanobubbles, 53 where the interaction between nanobubbles on a hydrophobic surface and cavitation microbubbles is seen. In that study, Borkent et al found experimentally that surface nanobubbles do not cavitate even for a sufficiently strong negative pressure, while cavitation bubbles originating from microscopic cracks are rapidly expanding.…”
Section: Discussionmentioning
confidence: 69%
“…If this scenario is true, prediction of the actual population of cavitation bubbles in practical situations will require that, among other things, one know not only the initial distribution of cavitation nuclei but also their dynamic behavior in which bubble-bubble interaction plays a significant role. Also, the present findings may be relevant to the study of the superstability of nanobubbles, 53 where the interaction between nanobubbles on a hydrophobic surface and cavitation microbubbles is seen. In that study, Borkent et al found experimentally that surface nanobubbles do not cavitate even for a sufficiently strong negative pressure, while cavitation bubbles originating from microscopic cracks are rapidly expanding.…”
Section: Discussionmentioning
confidence: 69%
“…With all these different methods they are found to behave differently than regular macroscopic bubbles. Surface nanobubbles behave peculiar in several ways: their contact angle is always much lower than expected from Young's law [8,9], they are stable against violent decompression [10], and in particular they are stable for much longer than expected: For such small bubbles one would expect a lifetime of order µs, due to the high Laplace pressure inside the bubbles which drives the gas into the liquid. On this last question many explanations were proposed, ranging from contamination that shields or limits the diffusive outflux of gas [11] to a dynamic equilibrium situation where lost gas is replenished [12,13].…”
mentioning
confidence: 95%
“…However, the gas more or less reverts into the nuclei during the tensile stressing, and the high tensile strength is lost again when the tensile tail dies away. This explains observations of Borkent et al (2007) interpreted as superstability of surface nanobubbles, and shows that a conventional medical lithotripter pulse is not suited for tensile strength measurement.…”
Section: Discussionmentioning
confidence: 68%